Kansas: Themes in Multicultural Adult Education Resonating Across the Nation, adult learning - Jeff Zacharakis; Gabriela Díaz de Sabatés; Dianne Glass (Educational Considerations, 2007)
Across the country in our communities, our schools, and our businesses, we are experiencing a cultural shift as new immigrants of many ethnic backgrounds arrive speaking different languages and adhering to different beliefs. From the beginning, the United States has always been a destination for people around the world seeking a better life.
Keywords: immigrants; multicultural; education; reasoning; adult learning; Kansas